Enhanced surveillance of a lymphogranuloma venereum outbreak in Sydney 2010-2012 - David J. Templeton; Kelly‐Anne Ressler; Kirsty Hope; Isobel M. Poynten (Elsevier, 2016)
Abstract Objectives: To investigate an increase in lymphogranuloma venereum (LGV) notifications in New South Wales (NSW). Methods: Enhanced surveillance of notified LGV cases in NSW between May 2010 and April 2012 using doctor and patient questionnaires. Results: Thirty‐seven doctors who had diagnosed 67 (76%) of 88 notified anorectal LGV infections were interviewed. The majority (n=33, 89%) of treating doctors were formally trained and accredited in HIV management and prescribing, and most (n=32, 86%) worked in a public sexual health clinic or a general practice with a high caseload of men who have sex with men (MSM). All 67 cases were MSM who resided in inner‐city Sydney and all were serovar L2b. Anal symptoms had been present in 64 cases (96%, 95%CI 87-99%) for a median of 8 days (range 2-1,825) prior to presentation. Almost one‐third (n=20) had another concurrent STI diagnosed. Most (82%) of the 22 interviewed patients reported being HIV positive and having other STIs diagnosed over the past year. In the preceding month, all 22 men reported condomless anal sex and the median number of casual sexual partners was 5 (range 0-100). Conclusions: Characteristics of LGV cases in NSW are similar to those described worldwide, suggesting that a sexually adventurous subgroup of MSM are at particular risk of infection. Implications: Education of non‐sexual‐health clinicians on LGV risk factors, presentation, testing and management may allow more timely diagnosis and notification of contacts to reduce LGV transmission in the community.